Clinical Evaluation of a Real-Time PCR Assay for Simultaneous Detection of Helicobacter pylori and Genotypic Markers of Clarithromycin Resistance Directly from Stool - Marrero Rolon, Rebecca (J Clin Microbiol, 2021)
Helicobacter pylori infection is mainly diagnosed noninvasively, with susceptibility testing traditionally requiring endoscopy. Treatment is empirical, with clarithromycin-based triple therapy recommended where resistance rates are below 15%. Rising rates of clarithromycin resistance, resulting in high clarithromycin-based therapy failure rates, are seen worldwide, but U.S. data are limited. We developed a real-time PCR assay for simultaneous detection of H. pylori and genotypic markers of clarithromycin resistance directly from stool specimens. The assay was validated by testing 524 stool samples using an H. pylori stool antigen test as the reference method for detection accuracy and Sanger sequencing to confirm genotypic susceptibility results. A separate set of 223 antigen-positive stool samples was tested and retrospective medical record review conducted to define clinical utility. PCR resulted in 88.6% and 92.8% sensitivity in the validation and clinical study sets, respectively. Sequencing confirmed correct detection of clarithromycin resistance-associated mutations in all positive validation samples. The PCR-predicted clarithromycin resistance rate was 39% in the clinical data set overall and 31% in treatment-naive patients; the clarithromycin-based triple therapy eradication rate in treatment-naive patients was 62%. The clarithromycin-based triple therapy success was lower when resistance was predicted by PCR (41%) than when no resistance was predicted (70%; P = 0.03). PCR results were positive in 98% of antigen-positive stools from patients tested for eradication. The described PCR assay can accurately and noninvasively diagnose H. pylori, provide genotypic susceptibility, and test for eradication. Our findings support the need for susceptibility-guided therapy in our region if a clarithromycin-based regimen is considered.